Species diversity of Rhinebothrium Linton, 1890 (Eucestoda: Rhinebothriidea) from Styracura (Myliobatiformes: Potamotrygonidae), including the description of a new species - Trevisan, Bruna; Marques, Fernando P. L. (Zootaxa, 2017)
The present study contributes to the knowledge of the cestode fauna of species of Styracura de Carvalho, Loboda & da Silva, which is the putative sister taxon of freshwater potamotrygonids—a unique group of batoids restricted to Neotropical freshwater systems. We document species of Rhinebothrium Linton, 1890 as a result of the examination of newly collected specimens of Styracura from five different localities representing the eastern Pacific Ocean and the Caribbean Sea. Overall, we examined 33 spiral intestines, 11 from the eastern Pacific species Styracura pacifica (Beebe & Tee-Van) and 22 from the Caribbean species S. schmardae (Werner). However, only samples from the Caribbean were infected with members of Rhinebothrium. Rhinebothrium tetralobatum Brooks, 1977, originally described from S. schmardae—as Himantura schmardae (Werner)—off the Caribbean coast of Colombia based on six specimens is redescribed. This redescription provides the first data on the microthriches pattern, more details of internal anatomy (i.e., inclusion of histological sections) and expands the ranges for the counts and measurements of several features. We describe a new species of Rhinebothrium from S. schmardae collected off the Caribbean coast of Panama. Rhinebothrium reydai n. sp. is diagnosed by possessing four testes per proglottid, acraspedote proglottids, single anterior-most and porterior-most loculi, and bothridia divided into 34–44 loculi. Collectively, these features distinguish the new species from all 41 species of Rhinebothrium currently recognized as valid, with the exception of R. chollaensis Friggens & Duszynski, 2005. The latter species, a parasite of Urobatis halleri (Cooper) from the eastern Pacific Ocean, has a similar morphology in comparison to R. reydai n. sp., but can be distinguished by being apolytic instead of euapolytic and by the morphology of the aporal lobe of the ovary, which reaches the mid-lateral margin of the cirrus sac, whereas in R. reydai n. sp. the aporal lobe only reaches the posterior margin, since the cirrus sac takes approximately ¾ of the proglottid in width. Also, in R. reydai n. sp., the first square proglottid occurs within the anterior third of the strobila (13–30%), whereas in R. chollaensis it occurs near the middle of the strobila (42–62%). Further, we discuss the patterns of infection and biogeographical distribution for species of Rhinebothrium in species of Styracura. The apparent disjunctive distribution of R. tetralobatum and R. reydai n. sp. in the Caribbean Sea throughout their host distribution, S. schmardae, and the absence of species of Rhinebothrium in the eastern Pacific sister-host, S. pacifica, reveal the importance of sample size and biogeographical representation for documenting the parasite fauna of host lineages.